A Single-Cell Transcriptome Profiling of Anterior Kidney Leukocytes From Nile Tilapia (Oreochromis niloticus) - Wu, Liting; Gao, Along; Li, Lan; Chen, Jianlin; Li, Jun; Ye, Jianmin (Frontiers in Immunology, 2021)
Teleost fish anterior kidney (AK) is an important haematopoietic organ with plentiful and multifarious immune cells, which is comparable in immune functions to mammalian bone marrow. Myeloid and lymphoid cells locate in AK, but the lack of useful specific gene markers and antibody-based reagents for the cell subsets makes the identification of different cell types difficult. The single-cell transcriptome sequencing enables single cell capturing and individual library construction, making the study on teleost fish AK immune cell heterogeneity possible. In this study, we performed the transcriptional pattern of 11,388 AK leukocytes with 10× Genomics single-cell RNA-seq (scRNA-seq). A total of 22 clusters corresponding to five distinct immune cell subsets were identified, including B cells, T cells, granulocytes, macrophages and dendritic cells (DCs). However, subsets of myeloid cells (granulocytes, macrophages and DCs) were not identified more detailed according to the known specific markers even though significant differences existed among the clusters. Then, we highlighted the B cell subsets and identified them as pro/pre B, immature/mature B, activated B/plasmablast and plasma cell based on the different expression of transcription factors (TFs) and cytokines. Clustering of differentially modulated genes by pseudotemporal trajectory analysis of B cell subsets showed that distinct kinetics of TFs responses to cell conversion. Moreover, we classified the T cells and discovered that CD3+CD4-CD8-, CD3+CD4+CD8+, CD4+CD8- and CD4-CD8+ T cells existed in AK, but neither CD4+CD8- nor CD4-CD8+ T cells can be further classified into subsets based on the known TFs and cytokines. Pseudotemporal analysis demonstrated that CD4+CD8- and CD4-CD8+ T cells belonged to different states with various TFs that might control their differentiation. The data obtained above provide us with the valuable and detail resource to uncover the leukocyte subsets in Nile tilapia AK, as well as more potential markers for identifying the myeloid and lymphoid cell types.